A Ce‐UiO‐66 Metal–Organic Framework‐Based Graphene‐Embedded Photocatalyst with Controllable Activation for Solar Ammonia Fertilizer Production. Issue 37 (25th July 2022) - Liu, Sixiao; Teng, Zhenyuan; Liu, Hang; Wang, Tianyi; Wang, Guoxiu; Xu, Qiang; Zhang, Xiuyun; Jiang, Min; Wang, Chengyin; Huang, Wei; Pang, Huan
Abstract: Currently, nitrogen fertilizers feed half of the global population, but their use is limited by energy consumption and transportation. Therefore, it is important to study photocatalysts for use in solar nitrogen fertilizers. Herein, a new type of graphene‐embedded Ce‐based UiO‐66 (Ce‐UiO‐66) photocatalyst (GSCe) is investigated. Ce‐UiO‐66 is activated by the breakage of benzene‐C bonds and the formation of active sites by ultraviolet light in water. Moreover, embedding graphene effectively controls activation and improves nitrogen fixation. GSCe exhibited a remarkable apparent quantum efficiency (AQE) of 9.25 % and stability under 365 nm light with solar‐level intensity. GSCe also performed well as a solar ammonia fertilizer for crop cultivation. This investigation opens up opportunities for nitrogen fixation photocatalysts to be used as environmentally friendly solar nitrogen fertilizers. Abstract : Activated graphene‐embedded Ce‐UiO‐66 catalysts showed a remarkable nitrogen fixation apparent quantum efficiency (AQE) of 9.25 % under 365 nm light and high stability as solar nitrogen fertilizer. Ce‐UiO‐66 is activated by the breakage of benzene‐C bonds and forms effective active sites. Graphene embedding controlled bond breakages and improved photocatalytic performance.